Productive performance of weanling piglets was improved by administration of a mixture of bacteriophages, targeted to control Coliforms and Clostridium spp. shedding in a challenging environment. Issue 5 (26th September 2016) - Hosseindoust, A. R.; Lee, S. H.; Kim, J. S.; Choi, Y. H.; Kwon, I. K.; Chae, B. J.
Summary: This study was conducted to investigate the effects of bacteriophages in different environments on growth performance, digestibility, ileal and caecal microbiota, gut morphology and immunity of weanling pigs. Two hundred piglets were randomly assigned to four treatment groups with five replicate pens with 10 pigs per pen. A 2 × 2 factorial arrangement of treatments was used to investigate the response of weanling pigs to supplemental bacteriophages (0 and 1.0 g/kg of diet) in contaminated or hygienic environments. Bacteriophages supplementation did not affect average daily gain (ADG), average daily feed intake (ADFI) and gain:feed in phases I and III; however, there was a significant improvement in ADG and gain:feed in phase II. The supplementation of bacteriophages increased the overall gain:feed of pigs. The overall result showed a greater ADG and ADFI in hygienic room. There were reductions in population of both ileal (p < 0.05) and caecal (p < 0.01) Clostridium spp. and ileal coliforms (p < 0.01) with the inclusion of bacteriophages in the diet. Bacteriophages increased ileal Lactobacillus and caecal Bifidobacterium and tended to increase ileal Bifidobacterium (p = 0.08). Contaminated environment decreased ileal Lactobacillus and caecal Bifidobacterium and tended to increase ileal Clostridium (p = 0.08) and coliforms (p = 0.08). Total anaerobic bacteria was tended to decrease (p = 0.06) in contaminated environment. Jejunal villus height increased in pigs received bacteriophages, but they did not affect other morphological items. The interaction between bacteriophages and environment tended to be significant (p = 0.06) for ileal villus height and ileal villus height to crypt depth ratio. The overall faecal score was significantly greater in hygienic environment and bacteriophages groups. The present findings indicate that there is an interactive effect on feed efficiency between bacteriophages and contaminated environment. In addition, bacteriophages improve jejunum morphology, and intestinal microbiota of pigs.